EVALUASI PROGRAM PENDIDIKAN KESETARAAN PAKET B UNTUK MENDUKUNG WAJAR DIKDAS 9 TAHUN DI KABUPATEN GORONTALO - Abdul Rahmat (Jurnal Ilmiah Visi, 2011)
At The research is aimed at describing the implementation of equity education evaluation program of equity education paket B for wajar dikdas 9th year at sub province Gorontalo. Design of this research is qualitative with use phenomenology approach and design multi cases. Base of decided to use this approach is (1) this research have been done at nature background and two sided background different case; (2) this research use human as important instrument; (3) this research more focus to process, not result. For implementation this multi cases studies as base as opinion that multi cases studies is a study with detail with two or more background with have different characteristic, a subject, documents or a happen. This research use snowball sampling technic, (1) deep interview; (2) participation observation; (3) documentation study. Informer decided with purposive technic source triangulation, And than did evaluation of credibility, dependability, and confirmability. Data analysis include: (1) case individual analysis and (2) analysis multicases. Result of this research is (1) Content program: (a) curriculum centered, (b) application for skill, (c) program purpose to student potential. (2) Learning: (a) community centre, (b) environment student, (c) program structural flexsibility, (d) student centered, (e) user resourch. (3) Program assurance: (a) innisiative organization and participative student and decentralitation, (b) democrazy.